Organization and Management of Non-Government Preschool Educational Organizations - Abdusalyamov Abdurakhman Abdumajidovich (Peerian Journals Publishing, 2022)
The progress of our rapidly developing country depends directly on the education of the young generation. As a type of educational organization, a non-governmental preschool educational organization has common features related to a good focus on the upbringing, education, development and health of children. This article discusses the content of organizing non-state preschool educational organizations and improving their activities.
Keywords: Non-governmental preschool education organization; charter; child; educator